2019
DOI: 10.1096/fj.201901743r
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin U suppresses insulin secretion by triggering mitochondrial dysfunction and endoplasmic reticulum stress in pancreatic β‐cells

Abstract: Neuromedin U (NMU), a highly conserved peptide in mammals, is involved in a wide variety of physiological processes. NMU, which is synthesized in β‐cells and co‐localizes with insulin, directly acts on β‐cells via NMU receptor 1 (NMUR1) to suppress glucose‐stimulated insulin secretion (GSIS). The mechanism underlying this insulinostatic effect has yet to be elucidated. We observed that NMU caused mitochondrial dysfunction by impairing mitochondrial biogenesis, respiration, and mitochondrial Ca2+ uptake in β‐ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
(185 reference statements)
0
8
0
Order By: Relevance
“…Moreover, NMS is an isoform of NMU and plays many physiological roles similar to NMU by binding to NMUR1 and NMUR2. As reported, NMU can act directly on β cells through NMUR1 to affect insulin secretion [ 26 , 27 ], and both NMU and NMS can regulate the synthesis and release of LH and FSH from the pituitary through NMUR2 [ 24 , 28 , 29 ]. These results suggest that NMS may regulate different types of hormones through different receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NMS is an isoform of NMU and plays many physiological roles similar to NMU by binding to NMUR1 and NMUR2. As reported, NMU can act directly on β cells through NMUR1 to affect insulin secretion [ 26 , 27 ], and both NMU and NMS can regulate the synthesis and release of LH and FSH from the pituitary through NMUR2 [ 24 , 28 , 29 ]. These results suggest that NMS may regulate different types of hormones through different receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A new perspective on the insulinostatic role of NMU is presented by the group of Zhang et al (40,110). These authors highlight the colocalization of NMU and insulin in pancreatic bcells.…”
Section: Pancreatic Isletsmentioning
confidence: 99%
“…It has been shown that rats have increased insulin sensitivity following NmU injection [ 66 ]. In another clinical study, it has been demonstrated that NmU suppresses glucose-induced insulin secretion through mitochondrial dysfunction and endoplasmic reticulum [ 67 ]. In our study, we observed that the NmU level was significantly lower in patients with NAFLD, but NmU was not identified as an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%